Oxidative stress in chronic renal allograft nephropathy in rats: effects of long-term treatment with carvedilol, BM 91.0228, or alpha-tocopherol - Göttmann, Uwe; Oltersdorf, Jens; Schaub, Meike; Knoll, Thomas; Back, Walter; Woude, Fokko J. van der; Braun, Claude (Journal of cardiovascular pharmacology, 2003)
Oxidative stress is markedly increased after kidney transplantation and may participate in the development and/or progression of chronic renal allograft nephropathy. In the present study we sought to assess the nephroprotective potential of antioxidative treatment in renal allograft recipients. Experiments were performed in the Fisher-Lewis rat model of chronic renal allograft nephropathy, with isografted Lewis rats serving as controls. Allografted rats were orally treated with carvedilol, an antihypertensive drug with antioxidative properties (25 mg/kg/d), its purely antioxidative derivative BM 91.0228 (5 mg/kg/d), alpha-tocopherol (100 mg/kg/d), a combination of propranolol/doxazosine (10/5 mg/kg/d), or vehicle for 24 weeks. At the end of the study, oxidative status and influence of antioxidative treatment were assessed in transplanted animals. Chronic allograft nephropathy was characterized by a marked increase of markers for oxidative stress (increased plasma and kidney levels of malondialdehyde, reduced glutathione, and tocopherol levels in renal allografts). Treatment with carvedilol, BM 91.0228, and tocopherol significantly improved antioxidative status of allograft kidney recipients. In addition, carvedilol reduced elevated blood pressure in allografted rats. However none of the drugs had a beneficial influence on functional and morphologic renal changes. Our data thus demonstrate that long-term treatment with the antioxidants carvedilol, BM 91.0228, or alpha-tocopherol does not prevent development of chronic transplant nephropathy, despite an improvement of antioxidative status.
Gesehen am 24.06.2022